Discursive dimension of the construction and the circulation of knowledge connected with the issue of foreign language teacher education within the Polish glottodidactic community - ORCHOWSKA, IZABELA (Glottodidactica, 2017)
The paper concerns the discursive dimension of the construction and the circulation of knowledge connected with the issue of foreign language teacher education. A starting point for the discussion is the assumption according to which glottodidactics as a science is still perceived in a highly heterogenic way by members of the Polish glottodidactic community. Not only is the subject of glottodidactics so complex and interdisciplinary that the multitude of its possible interpretations does not allow us to decide on one common epistemological paradigm, but glottodidactic discourse is also very heterogeneous. The author of this article presents the conclusions from a metaglottodidactic analysis of articles covering the subject of foreign language teacher training which were published in Neofilolog in 1990–2010, and answers the question of whether, and with what kind of discourse configurations do Polish glottodidacticians theoretically locate their propositions for educating teachers presented in their publications.